National Wealth and NNP and Natural Resources and National Wealth and NNP - John M. Hartwick (Queen's University, Department of Economics, 1993)
Corresponding to current national wealth as discounted future optimal consumption (Weitzman [1976]) we observe current national wealth to be the value of net accumulated stocks of capital. It follows that NNP can be interpreted as interest on national wealth. A constant value of wealth implies no net investment and NNP equals the value of consumption, the Hicksians notion of "income" We introduce natural resources into competitive dynamic general equilibrium models and examine the concepts of NNP and national wealth which are seen to sustain the efficient paths. This procedure leads to "formulas" for amending traditional statements of NNP in national accounting to allow for natural resource stock depletion and degradation. We consider depletion of exhaustible resource stocks and economics depreciation, pollution stock increase (and Pigovian taxes), renewable resource stock decline, and land use change (deforestation). This later inquiry leads to the appearance of capital gains in NNP. In the end we consider an oil exporter's NNP and optimal investment strategy for exhaustible resource rents. Throughout, we link NNP to the formal mnotion of national wealth or the value of accumulated capital.
Keywords: 330